High‐Performance Directional Water Transport Using a Two‐Dimensional Periodic Janus Gradient Structure. Issue 12 (30th October 2022) - Xie, Dongdong; Zhang, Bao Yue; Wang, Guilian; Sun, Yunna; Wu, Chaofeng; Ding, Guifu
Abstract: Numerous materials in micro‐ or nanoscale hierarchical structures with surface gradients serve as the enablers in directional liquid transportation. However, concurrent high‐speed and long‐range liquid transport is yet to be fully realized so far. Here, an overall‐improved approach is achieved in both water transport distance and velocity aspects using a 2D periodic Janus gradient structure, which is inspired by the Janus‐wettable desert beetle back, tapered asymmetric cacti spine, and periodic Nepenthes alata microcavity. This 2D channel can efficiently regulate the kinetics of liquid transport within its confined structure, in which the terminal potential well and periodic Janus topological structure enable sustaining water propelling through a long distance. In addition, the rapidly formed aqueous film facilitates a high initial momentum and fast transport of liquid droplets along the channel, achieving an averaged velocity of over 400 mm s −1 and a maximum normalized transport distance of 23.4 for a 3 µL droplet, as well as an ultralow liquid volume loss of 6.02% upon high‐flux water transport. This scalable, controllable, and easy‐fabricable 2D water transport system provides an insightful pathway in realizing high‐performance water manipulation and possibly facilitates substantial innovative applications in multidisciplinary fields. Abstract : A 2D bioinspired water transport system with periodic Janus gradient structure demonstrates a long‐range, ultrafast, and directional water propel approach with an averaged velocity of over 400 mm s −1 and a maximum normalized transport distance of 23.4 for a 3 µL droplet, as well as an ultralow volume loss of ≈6.02% upon high‐flux water transport.